Social Construction of Politics and Religion:Study of 2024 Election Jingles in Surabaya City KPU Environment - Harrel Ciddan; Nur Khairun Nisa; Khuzaimah Khuzaimah (Journal of Religion, Local Politics, and Law, 2025)
The 2024 Election Jingle "Choosing for Indonesia" is used by the Surabaya City General Election Commission (KPU) as a means of communication to support the Election's spirit. This study aims to understand the construction of the jingle playback in the internal environment of the Surabaya City KPU through a phenomenological approach and Peter L. Berger's social construction theory. The study examines three main stages—externalization, objectification, and internalization—regarding how a jingle is a communication and motivational tool. Data were collected through observation, interviews, and documentation from four informants at the Surabaya City KPU. The jingle playback illustrates a social construction process, with regular playbacks promoting democratic values similar to religious teachings.Objectification occurs as the jingle integrates into organizational culture, symbolizing collective identity and shared values, much like religious symbols in people's lives. Internalization is reflected in individuals' varying interpretations of the jingle, inspiring some to conform to its message while others engage differently. This process highlights how values of fairness and participation are embedded in personal and organizational identities. Regularly playing the jingle at 10 am and 3 pm boosts enthusiasm, awareness of democratic principles, and solidarity among KPU employees, similar to how religious rituals reinforce commitment to moral values.